Functionalized covalent triazine frameworks as promising platforms for environmental remediation: A review - Sina Pourebrahimi; Majid Pirooz (Cleaner Chemical Engineering, 2022)
Covalent triazine frameworks (CTFs), an emerging subclass of contemporary high-performance nanoporous materials, have demonstrated their plausible potential in diverse real-world applications, for instance, adsorption, separation, catalysis, energy storage, photonics, and electronics. Similar to other supermolecular structures such as metal-organic frameworks (MOF) and covalent organic frameworks (COFs), CTFs feature pre-designability and post-synthetic chemical tunability. Thus, they deliver distinct physicochemical, optical, electrical, and structural characteristics. Such features also endow CTFs with unique properties, including optional building blocks and synthetic methods, increased specific surface area, considerable pore volume, accessible micro-and/or mesopores in their structures, superior chemical/thermal stability, and heteroatom effect. Meanwhile, to further improve the performance of CTFs in practice and thus expand their possible applications, several CTFs comprising various functionalities have been successfully synthesized. CTFs can be modified via either bottom-up (i.e., pre-synthetic) or post-synthetic functionalization strategies and be used in environmental remediation implementations. In the present review, current developments in the environment-related applications of functionalized CTFs, including CO2 capture, removal of heavy metal species from aqueous solutions, radioiodine capture, uptake, and photocatalytic degradation of organic pollutants, are discussed in detail. Functionalized CTFs have shown unprecedented adsorption capacity and selectivity towards environmental pollutants. It has been revealed that the main interaction mechanisms between the adsorbate species and the functionalized CTFs' surfaces are electrostatic, acid-base, charge transfer, ion exchange, chelation, coordination, hydrogen-bonding, hydrophobic effect, and π−π stacking mechanisms. Meanwhile, more research is required to bridge the gap between lab-scale and real-world applications of functionalized CTFs in environmental remediation.